2019
DOI: 10.3390/vaccines7040134
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage among Registered Nurses in China during 2017–2018: An Internet Panel Survey

Abstract: Influenza vaccination is recommended for nurses in China but is not mandatory or offered free of charge. The main objective of this study was to determine influenza vaccination coverage and the principal factors influencing influenza vaccination among nurses in China. During 22 March–1 April 2018, we conducted an opt-in internet panel survey among registered nurses in China. Respondents were recruited from an internet-based training platform for nurses. Among 22,888 nurses invited to participate, 4706 responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Self-protection, patient protection, and family protection were the main reasons for influenza vaccine uptake in the vaccinated group; recommendations by the Ministry of Health were the reasons for vaccination only in 43.4% of the participants. Several studies, consistent with the present study, reported self-protection as the primary motivating factor of vaccination; however, there were inconsistencies with the present study results as patient protection was less motivating (22,28,33,34). According to a review study, 23 out of 40 studies found that self-protection and family protection were the most common reasons for influenza vaccine uptake (35).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Self-protection, patient protection, and family protection were the main reasons for influenza vaccine uptake in the vaccinated group; recommendations by the Ministry of Health were the reasons for vaccination only in 43.4% of the participants. Several studies, consistent with the present study, reported self-protection as the primary motivating factor of vaccination; however, there were inconsistencies with the present study results as patient protection was less motivating (22,28,33,34). According to a review study, 23 out of 40 studies found that self-protection and family protection were the most common reasons for influenza vaccine uptake (35).…”
Section: Discussionsupporting
confidence: 58%
“…According to a review study, 23 out of 40 studies found that self-protection and family protection were the most common reasons for influenza vaccine uptake (35). Some authors stated that to improve vaccination coverage in healthcare personnel, highlighting self-protection and family protection as a personal gain is more effective than patient protection as a moral consideration or organizational regulation (33,34).…”
Section: Discussionmentioning
confidence: 99%
“… 5 See Kolenikov (2014) for a theoretical discussion of the iterative proportional fitting method and Stata application, and Lusk and Marette (2010) ; Ward et al (2011) ; Alemi et al (2018) ; Huang et al (2019) , and Yu et al (2019) for recent applications. …”
mentioning
confidence: 99%
“…Of the 54 included studies, 44 were cross-sectional studies (see Additional file 2). Study locations were North America (n = 32) [5,, Asia (n = 9) [42][43][44][45][46][47][48][49][50], Europe (n = 7) [51][52][53][54][55][56][57], Australia (n = 4) [58][59][60][61], worldwide population (n = 1) [62], and an unspecified location (LinkedIn members) (n = 1) [63]. See Figure 2 for the distribution of included studies by country.…”
Section: Study Characteristicsmentioning
confidence: 99%